Ruthenium Olefin Metathesis Catalysts Systematically Modified in Chelating Benzylidene Ether Fragment: Experiment and Computations. Issue 32 (20th August 2018) - Zieliński, Adam; Szczepaniak, Grzegorz; Gajda, Roman; Woźniak, Krzysztof; Trzaskowski, Bartosz; Vidović, Dragoslav; Kajetanowicz, Anna; Grela, Karol
Abstract : Five Hoveyda–Grubbs‐type complexes bearing cyclopropyl to cycloheptyl ether moieties in the chelating benzylidene ligand have been synthesized and investigated by spectroscopic and crystallographic methods. Their experimentally measured catalytic activity in model ring‐closing metathesis (RCM) reactions was studied at catalyst loading down to 10 ppm and compared with DFT calculations. The latter can be used as a reliable and accurate guidance in the fast and inexpensive design of new metathesis catalysts, as we were able to find a good correlation between the initiation rate and free‐energy barrier of the reaction. Abstract : The synthesis of Ru complexes with cyclic ether moieties in the chelating benzylidene ligand is presented. The relationship between the structure of the ether fragment and the activity of the complex was investigated theoretically and experimentally.